Lepisorus youxingii (Polypodiaceae), a new fern species from Guangxi, China - Jiang, Ri-Hong; Wang, Ya-Rong; Zhang, Xian-Chun (Phytotaxa, 2020)
Lepisorus youxingii, a new fern of Polypodiaceae from southern China, is described and illustrated. Morphological comparison with L. thunbergianus, L. oligolepidus, and L. lewisii is provided. Both morphological and molecular evidences clearly indicate that L. youxingii is a distinct species. It differs in rhizome scales (brown, iridescent, transparent, lanceolate with broadly ovate base, margin denticulate, and apex long acuminate), laminae (lanceolate, widest at third from the base, base attenuate, decurrent, with margin narrowly callose, and apex long caudate), and paraphyses (brown, orbicular, with margin denticulate, and lumina transparent). This species is in protected area with more than 250 mature individuals and it can be classified as LC (Least Concern) according to IUCN criteria.